Evaluasi Toleransi Plasma Nutfah Padi Lokal pada Lahan Masam Kahat Fosfor - Tintin Suhartini; Dwinita W. Utami; Ida Hanarida (Buletin Plasma Nutfah, 2013)
Phosporus (P) deficiency is one oflimiting factor for rice growth. In Indonesia P deficiency muchoccurs in acid soils. The use of P deficiency tolerant varietiesis the best solution compared to the application of P fertilizerdue to more efficient in cost. The purpose of this study was toevaluate the local rice germplasm collected from severalregions in Indonesia to P deficiency in acid soil. The study wasconducted in Jasinga West Java during wet season of 2006-2007 with the soil condition lack of P. The experiments wereconducted with the two treatments: first, without P fertilizerand second with P fertilizer equivalent of 25 kg P/ha. The total100 accessions of rice germplasm were screened in this fieldbased on a randomized block design with three replications.Fertilizing were given on experiments I and II with thecomposition: urea 300 kg/ha and 100 kg KCl. The field designwas done by plotting size is 1 x 5 m2, spacing plant of 25 cm x25 cm, and planting two seeds per hole. The yield componentscharacters which were observed: number of tillers, plant dryweight, plant height and flowering. The results of combinedanalysis showed that there is a significant interaction betweenP and genotype on the tiller number, whereas the dry weight ofplant, plant height, and flowering were is not significant. Theevaluation of 100 local rice genotypes to P deficiency byindicators of the tiller number and dry weight of plantsobtained 19 genotypes that are tolerant to P deficiency with therelative value of tillers number and dry weight of plants morethan 80%. Local varieties Mandalet, Ganefo, Padi Belanda,Pulut Jangan, Padi Ubek Bala, and Padi Krayan were the mosttolerant to conditions without P which showed the tillersnumber more 1-21% rather than the conditions with Pfertilizer. There are three selected genotypes, Pulut Jangan,Padi Ubek Bala, and Padi Krayan which increased the numberof tillers and dry weight of plants in without P conditions. Theincreasing of tillers number were reach 1-17% while the dryweight increased 12-41%.